Reassessment of the taxonomic status of Canis antiquus (Carnivora, Canidae) from the Early Pleistocene site of Minnaar’s Cave (Gauteng, South Africa) - (:unkn) unknown (My University, 2024)
Despite an extensive fossil record, the Plio-Pleistocene canids of South Africa remain little studied compared to other carnivore guilds (felids and hyenids). Minnaar’s Cave (Gauteng, South Africa) is a paleontological site dated ca. 2 Ma. In 1937, Broom identified a new jackal-like species, Canis antiquus. The species was never re-identified elsewhere, despite the fossil richness of the other Cradle of Humankind sites and the abundance of medium-sized canids in the assemblages. The present paper reassesses the taxonomic status of C. antiquus in the light of consistent modern and fossil comparison samples for the two species of African jackal (Lupulella mesomelas and Lupulella adusta) as well as raccoon dog (Nyctereutes procyonoides, Nyctereutes terblanchei) and Nyctereutes-like species (Canis brevirostris). The paleontological study highlights the considerable morphometric variability of medium-sized canids, which means that a part of individuals shares similarities from one species to another. Nevertheless, the co-occurrence of diagnostic criteria for different anatomical elements (e.g., various teeth) enables specific identification. Our study invalidates the existence of C. antiquus and reassigns the fossils to L. adusta. The study of the Minnaar’s Cave specimens contributes to highlighting the presence of L. adusta in the Plio-Pleistocene assemblages of South Africa, previously considered scarce.
Keywords: African Research